Aboveground herbivory does not affect mycorrhiza-dependent nitrogen acquisition from soil but inhibits mycorrhizal network-mediated nitrogen interplant transfer in maize - He, Chenling; Lin, Yibin; Zhang, Yifang; Tong, Lu; Ding, Yuanxing; Yao, Min; Liu, Qian; Zeng, Rensen; Chen, Dongmei; Song, Yuanyuan (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal fungi (AMF) are considered as biofertilizers for sustainable agriculture due to their ability to facilitate plant uptake of important mineral elements, such as nitrogen (N). However, plant mycorrhiza-dependent N uptake and interplant transfer may be highly con-text-dependent, and whether it is affected by aboveground herbivory remains largely unknown. Here we used 15N labeling and tracking to examine the effect of aboveground insect herbivory by Spodoptera frugiperda on mycorrhiza-dependent N uptake in maize (Zea mays L.). To minimize consumption difference and 15N loss due to insect chewing, insect herbivory was simulated by mechanical wounding + oral secretions of S. frugiperda larvae. Inoculation with Rhizophagus irregularis (Rir) significantly improved maize growth, and N/P uptake. The 15N labeling experiment showed that maize plants absorbed N from soils via the extraradical mycelium of mycorrhizal fungus and from the neighboring plant transferred by common mycorrhizal net-works (CMNs). The aboveground leaf simulated herbivory did not affect mycorrhiza-mediated N acquisition from soil. However, CMN-mediated N transfer from the neighboring plant was blocked by the leaf simulated herbivory. Our findings suggest that aboveground herbivory inhibits CMN-mediated N transfer between plants but did not affect N acquisition from soil solutions via extraradical mycorrhizal mycelium.